Translating Unconventional T Cells and Their Roles in Leukemia Antitumor Immunity - Nilberto Dias de Araújo; Fábio Magalhães Gama; Mateus de Souza Barros; Thaís Lohana Pereira Ribeiro; Fabíola Silva Alves; Lilyane Amorim Xabregas; Andréa Monteiro Tarragô; Adriana Malheiro; Allyson Guimarães Costa (Journal of Immunology Research)
Recently, cell-mediated immune response in malignant neoplasms has become the focus in immunotherapy against cancer. However, in leukemia, most studies on the cytotoxic potential of T cells have concentrated only on T cells that recognize peptide antigens (Ag) presented by polymorphic molecules of the major histocompatibility complex (MHC). This ignores the great potential of unconventional T cell populations, which include gamma-delta T cells (γδ), natural killer T cells (NKT), and mucosal-associated invariant T cells (MAIT). Collectively, these T cell populations can recognize lipid antigens, specially modified peptides and small molecule metabolites, in addition to having several other advantages, which can provide more effective applications in cancer immunotherapy. In recent years, these cell populations have been associated with a repertoire of anti- or protumor responses and play important roles in the dynamics of solid tumors and hematological malignancies, thus, encouraging the development of new investigations in the area. This review focuses on the current knowledge regarding the role of unconventional T cell populations in the antitumor immune response in leukemia and discusses why further studies on the immunotherapeutic potential of these cells are needed.